The Power of Contextual Effects in Forensic Anthropology: A Study of Biasability in the Visual Interpretations of Trauma Analysis on Skeletal Remains1. Issue 5 (26th March 2014) - Nakhaeizadeh, Sherry; Hanson, Ian; Dozzi, Nathalie
Abstract The potential for contextual information to bias assessments in the forensic sciences has been demonstrated, in several forensic disiplines. In this paper, biasability potential within forensic anthropology was examined by analyzing the effects of external manipulations on judgments and decision‐making in visual trauma assessment. Three separate websites were created containing fourteen identical images. Participants were randomly assigned to one website. Each website provided different contextual information, to assess variation of interpretation of the same images between contexts. The results indicated a higher scoring of trauma identification responses for the Mass grave context. Furthermore, a significant biasing effect was detected in the interpretation of four images. Less experienced participants were more likely to indicate presence of trauma. This research demonstrates bias impact in forensic anthropological trauma assessments and highlights the importance of recognizing and limiting cognitive vulnerabilities that forensic anthropologists might bring to the analysis.